Control optimization of multimode aerospace system get to the orbit, based on application of differential transformation - Гусинін, В. П.; Гусинін, А. В.; Тачиніна, О. М. (Problems of Informatization and Control, 2008)
The approach to control optimization of multimode aerospace system get to the orbit is offered. It’s based on application of the mathematical apparatus of differential transformations of functions and equations, does not require numerical integration of differential equations of path motion of aerospace system and allows for analytical examination of the problem